Preparation method and application of cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material
By constructing CdSe/CdS heterostructure on the CdS photoanode and loading TiN nanoparticles, two-dimensional structure photoelectrocatalytic materials of cadmium sulfide/cadmium selenide/titanium nitride were prepared, which solved the problem of low solar energy utilization rate and high photocarrier recombination in the photoelectrocatalytic decomposition of water and high photogenerating carrier recombination in the process of photoelectrocatalytic decomposition of water and hydrogen production, and achieved efficient photoelectrocatalytic decomposition of water and hydrogen production.
Patent Information
- Application Number
- CN202411921004.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-25
AI Technical Summary
In the process of photoelectro-catalytic decomposition of water hydrogen production, existing CdS photoanodes have problems such as low solar energy utilization, high photogenerated carrier recombination and serious photocorrosion.
By combining CdSe with CdS, a heterostructure with type-II energy level matching is constructed, and TiN nanoparticles are loaded on its surface, and two-dimensional structured photoelectrocatalytic materials are prepared by spin coating. This material achieves rapid separation and transmission of photogenerated carriers through the combination of hydrothermal method, continuous ion layer adsorption reaction method and spin coating method, extends the carrier life and broadens the light absorption range.
The efficiency of photoelectro-catalytic decomposition of water to produce hydrogen is significantly improved, the carrier life is extended, the light absorption range is widened, the photogenerated carrier recombination is reduced, and the photoelectrocatalytic performance is enhanced.
Smart Images

Figure CN119346159B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic photoelectric materials, and specifically relates to a preparation method and application of a cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectric catalytic material. Background Art
[0002] With the continuous development of urbanization and industrialization, the traditional fossil fuels on the earth are gradually consumed, which not only triggers an energy crisis, but also causes serious environmental problems. Therefore, it is crucial to find renewable alternative energy sources. Among these energy sources, hydrogen (H2) has high combustion calorific value and environmentally friendly characteristics, and is considered to be one of the most promising candidates for solving the growing energy demand and environmental challenges. Among various hydrogen production technologies, semiconductor photoelectrocatalytic water splitting technology has attracted widespread attention from countries around the world because it can directly use solar energy to produce green hydrogen. At present, one of the key challenges of this technology is the rational design and preparation of efficient and stable semiconductor photoanode materials.
[0003] Cadmium sulfide (CdS) is an n-type semiconductor with visible light response. It has low preparation cost, suitable bandgap width, and ideal conduction band potential (which is conducive to the conversion of H + Reduction to H2) and other advantages, it is considered to be one of the ideal photoanode materials for photoelectrocatalytic water decomposition. At present, CdS nanostructures of various sizes and morphologies have been used as photoanodes in the study of photoelectrocatalytic water decomposition and hydrogen production. Among these nanostructures, two-dimensional CdS nanostructures, especially two-dimensional nanosheet arrays grown on conductive substrates, have a high specific surface area and can provide more reactive sites for photoelectrocatalytic water decomposition reactions, and the ultra-thin two-dimensional nanosheet structure can shorten the transmission path of photogenerated carriers. Therefore, compared with one-dimensional CdS nanostructures, two-dimensional CdS nanostructures exhibit better photoelectrocatalytic performance. However, a single-component CdS photoanode can only absorb sunlight with a wavelength less than 520 nm (photon energy higher than 2.4 eV), resulting in low solar energy utilization efficiency. At the same time, the photogenerated carriers inside the CdS photoanode are easy to recombine, resulting in low light-to-hydrogen conversion efficiency. In addition, the accumulation of photogenerated holes in the CdS photoanode will cause S 2- The self-oxidation of CdS leads to photocorrosion when exposed to light, thus limiting the application of CdS photoanodes in the field of photoelectrocatalytic water decomposition to produce hydrogen.
[0004] In view of the above problems, from the perspective of improving the utilization rate of solar energy and the separation efficiency of photogenerated carriers, on the one hand, the n-type semiconductor cadmium selenide (CdSe) with a narrower bandgap can be combined with CdS to construct a heterostructure with type-II energy level matching, forming a photogenerated carrier directional transmission channel that is conducive to the migration of photogenerated electrons from CdSe to CdS and the migration of photogenerated holes from CdS to CdSe, thereby accelerating the separation and transfer of photogenerated carriers and greatly reducing the recombination of photogenerated carriers. At the same time, CdSe has a narrow bandgap (about 1.9 eV), which can effectively enhance the light absorption capacity of the heterostructure, improve the utilization rate of solar energy, and thus improve the photoelectrocatalytic performance of the heterostructure. On the other hand, the semiconductor photoanode can be modified with metal nanoparticles, and the surface plasmon resonance effect of metal nanoparticles can be used to regulate the light absorption range and provide hot electron injection to increase the number of photoelectrons; the Schottky junction formed at the interface between the metal and the semiconductor inhibits the recombination of photogenerated carriers and prolongs the carrier lifetime, so as to further improve the photoelectrocatalytic performance of the photoanode. However, although the currently widely used plasmon gold, silver and other precious metal nanoparticles have a strong surface plasmon resonance effect, their scarcity and high cost limit the practical application of traditional plasma photoanode materials. Titanium nitride (TiN), as a transition metal nitride with metal-like properties, has low preparation cost, good chemical stability, and a wide spectrum of surface plasmon resonance properties in the visible to near-infrared wavelength range. It is a promising alternative material for precious metal plasmas. In view of these unique advantages of TiN, it has been used to modify semiconductor photoanode materials to construct heterostructure photoanodes for photoelectrocatalysis and photocatalytic water decomposition to produce hydrogen. Unfortunately, as far as we know, there is no report on the use of CdS / CdSe / TiN two-dimensional structured photoelectrocatalytic materials for photoelectrocatalytic water decomposition to produce hydrogen. Summary of the invention
[0005] In view of the deficiencies of the above-mentioned prior art, the object of the present invention is to provide a method for preparing a cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material. The cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material prepared by the preparation method provided by the present invention can quickly separate and transmit photogenerated electron-hole pairs to prolong the lifetime of photogenerated carriers, broaden the light absorption range and improve the utilization rate of sunlight, generate hot electron injection and effectively inhibit the recombination of photogenerated charges, and ultimately achieve the purpose of improving its photoelectrocatalytic water decomposition efficiency to produce hydrogen.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] A method for preparing a cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material, comprising the following steps:
[0008] Step 1: Preparation of two-dimensional CdS nanosheet arrays using a one-step hydrothermal method
[0009] First, a CdSO4 aqueous solution is added to a beaker, and then ammonia water is added dropwise under stirring. During this process, the mixed solution first becomes turbid and then clear, and then stirring is continued to obtain a mixed solution A; then, hexadecyltrimethylammonium bromide (CTAB) is added to the mixed solution A, and stirring is continued to obtain a mixed solution B; then, a thiourea (CH4N2S) aqueous solution is added to the mixed solution B, and stirring is continued to obtain a mixed solution C; finally, the mixed solution C is transferred to the inner tank of the reactor, and the FTO conductive glass is placed in the inner tank of the reactor with the conductive surface facing downward and tilted to perform a hydrothermal reaction. After the hydrothermal reaction, the sample is taken out, washed with deionized water, and then dried to obtain a two-dimensional cadmium sulfide nanosheet array FTO@CdS;
[0010] Step 2: Preparation of two-dimensional CdS nanosheet array / CdSe nanoparticle heterostructures using a continuous ion layer adsorption reaction method
[0011] First, the FTO@CdS in step 1 is immersed in a Cd(NO3)2 solution, and then washed in anhydrous ethanol; after drying, the sample is immersed in a Na2SeO3 aqueous solution, and finally washed in deionized water. After such steps are repeated several times, a two-dimensional cadmium sulfide nanosheet array / cadmium selenide nanoparticle heterostructure FTO@CdS / CdSe is obtained;
[0012] Step 3: Preparation of cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material by spin coating
[0013] TiN nanoparticles were further loaded on the surface of FTO@CdS / CdSe by spin coating. First, TiN was dispersed in anhydrous ethanol and then ultrasonically treated to make it evenly dispersed to obtain a TiN precursor solution. Finally, 500 μL of the TiN precursor solution was vertically dropped on the surface of FTO@CdS / CdSe and spin coating was performed to obtain a cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material FTO@CdS / CdSe / TiN.
[0014] The chemical formula and English abbreviation in the technical scheme are explained as follows:
[0015] CTAB stands for hexadecyltrimethylammonium bromide, CH4N2S stands for thiourea;
[0016] FTO stands for fluorine-doped SnO2 conductive glass, CdS stands for cadmium sulfide, CdSe stands for cadmium selenide, and TiN stands for titanium nitride;
[0017] FTO@CdS represents two-dimensional cadmium sulfide nanosheet arrays grown on FTO conductive glass, and the subsequent deposited components are all carried out on this basis.
[0018] Preferably, in step 1, the concentration of the CdSO4 aqueous solution is 0.1 M, and the amount of the CdSO4 aqueous solution is (10-20) mL; the concentration of the ammonia water is 25wt%, and the amount of the ammonia water is (1-10) mL; the concentration of the CH4N2S aqueous solution is 0.1 M, and the amount of the CH4N2S aqueous solution is (10-20) mL; the amount of CTAB is (0.005-0.01) g.
[0019] Further preferably, in step 1, the amount of CdSO4 aqueous solution used is 18 mL; the amount of ammonia water used is 4 mL; the amount of CH4N2S aqueous solution used is 18 mL; and the amount of CTAB used is 0.0072 g.
[0020] Preferably, the hydrothermal condition of the reactor in step 1 is 80-150° C. for 10-40 min.
[0021] Further preferably, the hydrothermal condition of the reactor in step 1 is 100° C. for 30 min.
[0022] Preferably, in step 2, the solvent in the Cd(NO3)2 solution is a mixed solution of 30wt% water and 70wt% anhydrous ethanol.
[0023] Preferably, the specific steps of step 2 are as follows: first, immerse the FTO@CdS in step 1 in a 0.1 M Cd(NO3)2 solution for (10-30) s, and then wash in anhydrous ethanol for (10-30) s; after drying, immerse the sample in a 0.1 M Na2SeO3 aqueous solution at 70°C for (10-30) s, and finally, wash in deionized water for (10-30) s. After such cycles (10-50) times, a two-dimensional cadmium sulfide nanosheet array / cadmium selenide nanoparticle heterostructure FTO@CdS / CdSe is obtained.
[0024] Preferably, the contact time of each material in step 2 is 20 s, the temperature of the Na2SeO3 aqueous solution is (50-90)°C, and the number of cycles is (5-50) times.
[0025] Further preferably, the temperature of the Na2SeO3 aqueous solution in step 2 is 70°C and the number of cycles is 25 times.
[0026] Preferably, the average particle size of the TiN nanoparticles in step 3 is 20 nm;
[0027] Preferably, the concentration of the TiN precursor solution in step 3 is 0.2-0.6 mg / mL, and the ultrasonic condition is 100-200w for 20-60 min;
[0028] Further preferably, in step 3, the concentration of the TiN precursor solution is 0.4 mg / mL, and the ultrasonic condition is 100 W for 30 min.
[0029] Preferably, the spin coating conditions in step 3 are first spin coating at a low speed of (1000-2000) r / min for (10-20) s, and then spin coating at a high speed of (3000-4000) r / min for (20-40) s; the loading amount of TiN nanoparticles is adjusted by controlling the number of spin coating to (10~100) times.
[0030] Further preferably, the spin coating conditions in step 3 are firstly spin coating at a low speed of 1000 r / min for 10 s, and then spin coating at a high speed of 3000 r / min for 30 s; the number of spin coating is 60 times.
[0031] A cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectric catalytic material is prepared according to the above preparation method.
[0032] The above-mentioned cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material is used for photoelectrocatalytic decomposition of water to produce hydrogen.
[0033] Characterization Instruments
[0034] The crystal structure of the prepared samples was tested by Ultima U X-ray diffractometer (XRD) of Rigaku Corporation. The element distribution and valence state of the prepared samples were analyzed by ESCALAB 250XI X-ray photoelectron spectrometer (XPS) of Thermo Fisher Scientific, USA, with the signal of carbon with binding energy of 284.8 eV as reference. The morphology of the prepared samples was characterized by S-4800 field emission scanning electron microscope (SEM) of Hitachi, Japan and JEM-2100Plus transmission electron microscope (TEM) of JEOL. The light absorption characteristics of the prepared samples were analyzed by LAMBDA-950 UV-visible near-infrared spectrophotometer of PE Company, USA.
[0035] Photoelectric response test
[0036] The photoelectric response characteristics of the prepared samples were tested by Shanghai Chenhua CHI760e electrochemical workstation. In the three-electrode system, the prepared sample was used as the working electrode, the platinum wire was used as the counter electrode, and the silver / silver chloride electrode was used as the reference electrode. The electrolyte used was a mixed solution of 0.25 M Na2SO3 and 0.35 M Na2S. Argon was passed into the electrolyte for 20 min before the test to remove the dissolved oxygen in the electrolyte.
[0037] Photoelectrocatalytic hydrogen production
[0038] The photoelectrocatalytic hydrogen production activity of the prepared samples was tested in a side-radiated sealed reaction cell equipped with a calibrated hydrogen collection tube. For a typical photoelectrocatalytic hydrogen production process, 200 ml of deionized water containing sacrificial reagents (0.25 M Na2SO3 and 0.35 M Na2S) was added to the reaction cell, where S 2- / SO3 2- ions act as hole scavengers. Size: 1.5×2.0 cm 2 The sample was used as the working electrode, the platinum wire as the counter electrode, and the silver / silver chloride electrode as the reference electrode. The three electrodes were connected to the reaction cell. A 300 W xenon lamp was selected as the light source, and a UV cutoff filter (λ≥400 nm) was used to generate visible light irradiation. The light emitted by the xenon lamp was vertically irradiated onto the sample electrode through the quartz window on the side of the reaction cell. At room temperature, the hydrogen produced in the closed reaction cell was collected into a scaled hydrogen collection tube using the drainage method, and the volume of hydrogen produced in the reaction cell was measured by the scale on the hydrogen collection tube.
[0039] Compared with the prior art, the present invention has the following advantages:
[0040] (1) The present invention ingeniously combines the hydrothermal method, the continuous ion layer adsorption reaction method and the spin coating method to prepare a cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material integrating type-II energy level matching, surface plasmon resonance effect and Schottky junction;
[0041] (2) The present invention utilizes the excellent visible light absorption performance of CdSe and the wide-spectrum surface plasmon resonance effect of TiN to improve the utilization rate of solar energy; and utilizes the type-II energy level matching formed at the interface of CdS and CdSe to promote the separation and transmission of photogenerated carriers;
[0042] (3) The present invention utilizes the surface plasmon resonance effect of non-metallic TiN to induce hot electron injection and increase the number of photoelectrons; utilizes the Schottky junction formed at the interface of TiN and CdS to inhibit the recombination of photogenerated carriers, prolong the carrier lifetime, and significantly enhance the performance of photoelectrocatalytic water decomposition to produce hydrogen;
[0043] (4) The preparation process of the present invention is simple, the purity of the synthesized material is high, the size is at the nanometer level, and the raw materials used are cheap, which is suitable for the field of photoelectrocatalytic water decomposition to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a flow chart for preparing the cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material prepared in an embodiment of the present invention.
[0045] Figure 2This is an X-ray diffraction spectrum of the cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material prepared in an embodiment of the present invention.
[0046] Figure 3 X-ray photoelectron spectra of the cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material prepared in accordance with an embodiment of the present invention: (a) full XPS spectrum, (b) high-resolution XPS spectrum of Cd 3d, (c) high-resolution XPS spectrum of S 2P, (d) high-resolution XPS spectrum of Se 3d, (e) high-resolution XPS spectrum of Ti 2P, and (f) high-resolution XPS spectrum of N 1S.
[0047] Figure 4 Scanning electron microscope images of the cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structured photoelectrocatalytic material prepared in accordance with an embodiment of the present invention: (a, b) SEM images of cadmium sulfide, (c, d) cadmium sulfide / cadmium selenide, and (e, f) SEM images of cadmium sulfide / cadmium selenide / titanium nitride.
[0048] Figure 5 Transmission electron microscopy morphology, high resolution and element distribution map of the cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material prepared in accordance with an embodiment of the present invention: (a) TEM image, (b) HRTEM image, (c) HAADF-STEM image, and (dh) corresponding EDX element distribution map.
[0049] Figure 6 Photoresponse characteristic diagram of the cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material prepared in an embodiment of the present invention: (a) light absorption curve and (b) light capture efficiency curve.
[0050] Figure 7 Photoelectric performance diagram of the cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectric catalytic material prepared in accordance with an embodiment of the present invention: (a) instantaneous photocurrent density curve, (b) linear sweep voltammetric characteristic curve, and (c) comparison curve of photoelectric conversion efficiency with applied bias voltage.
[0051] Figure 8 The hydrogen production performance diagram of the cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectric catalytic material prepared in the embodiment of the present invention: (a) hydrogen production amount and (b) hydrogen production rate comparison curve.
[0052] Fig. 9 Schematic diagram of the principle of realizing high-performance photoelectrocatalytic water decomposition to produce hydrogen using the cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material prepared in an embodiment of the present invention. DETAILED DESCRIPTION
[0053] In order to make the contents of the present invention easier to understand, the technical solutions of the present invention are further described below in conjunction with specific implementation methods. However, the embodiments are intended to explain the present invention and cannot be understood as limiting the present invention.
[0054] Example
[0055] Step 1: Preparation of 2D CdS nanosheet arrays using a simple one-step hydrothermal method
[0056] First, 18 mL of 0.1 M CdSO4 aqueous solution was added to a 100 mL beaker, and then 4 mL of ammonia water was slowly added dropwise under stirring. During this process, the mixed solution first became turbid and then clarified, and then continued to stir for 5 min to obtain a mixed solution A; then, 0.0072 g of hexadecyltrimethylammonium bromide CTAB was added to the mixed solution A, and continued to stir for 20 min to obtain a mixed solution B; then, 18 mL of 0.1 M thiourea CH4N2S aqueous solution was added to the mixed solution B, and continued to stir for 2 min to obtain a mixed solution C; finally, the mixed solution C was transferred to a dry reactor liner, and the cleaned FTO conductive glass was placed in the reactor liner with the conductive surface facing down. After hydrothermal reaction in a constant temperature heating box at 100°C for 30 min, the sample was taken out, rinsed with deionized water, and then dried naturally to obtain a two-dimensional cadmium sulfide nanosheet array FTO@CdS;
[0057] Step 2: Preparation of two-dimensional CdS nanosheet array / CdSe nanoparticle heterostructures using a continuous ion layer adsorption reaction method
[0058] First, the FTO@CdS in step 1 was immersed in a 0.1 M Cd(NO3)2 solution (solvent: 30 wt% water + 70 wt% anhydrous ethanol) for 20 s, and then washed in anhydrous ethanol for 20 s; after natural drying, the sample was immersed in a 0.1 M Na2SeO3 aqueous solution at 70°C for 20 s, and then washed in deionized water for 20 s. This process was recorded as one cycle, and the cycle was repeated 25 times; finally, the sample electrode was dried in a vacuum drying oven at 60°C for 1 h to obtain a two-dimensional cadmium sulfide nanosheet array / cadmium selenide nanoparticle heterostructure FTO@CdS / CdSe.
[0059] Step 3: Preparation of cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material by spin coating
[0060] TiN nanoparticles (average particle size of 20 nm) were loaded on the surface of FTO@CdS / CdSe by spin coating. First, 40 mg of TiN nanoparticles were dispersed in 100 mL of anhydrous ethanol, and then ultrasonicated in an ultrasonic machine with a power of 100 W for 30 min to make them uniformly dispersed, and a TiN precursor solution with a concentration of 0.4 mg / mL was obtained. Then, 500 μL of the prepared TiN precursor solution was measured with a pipette and slowly dropped vertically on the prepared FTO@CdS / CdSe surface, and the coating was rotated at a low speed of 1000 r / min for 10 s, and then at a high speed of 3000 r / min for 30 s. This process was recorded as one cycle, and the cycle was repeated 60 times; finally, the spin-coated sample electrode was dried in a vacuum drying oven at 60 ° C for 1 h to obtain the cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material FTO@CdS / CdSe / TiN.
[0061] The following is a discussion of the results of the testing of the materials of the present invention in combination with the characterization data.
[0062] The following are the composition, morphology characterization and photoelectrocatalytic performance test results of the cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material prepared in the example. The FTO substrate is not marked in the figure, but it exists.
[0063] Figure 1 The preparation flow chart of the cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material prepared in the embodiment of the present invention shows that the cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material integrating type-II energy level matching, surface plasmon resonance effect and Schottky junction is prepared by ingeniously combining hydrothermal method, continuous ion layer adsorption reaction method and spin coating method.
[0064] Figure 2 The X-ray diffraction spectrum is shown in Figure 1. As can be seen from the figure, the diffraction peak of the prepared CdS matches well with the standard card JCPDS (80-0019) of cubic phase CdS, and there is no impurity peak in the sample, indicating that the prepared CdS has high purity; the diffraction peak of the prepared CdS / CdSe has a characteristic diffraction peak that matches the standard card JCPDS (77-0046) of CdSe; the diffraction peak of the prepared CdS / CdSe / TiN does not detect obvious characteristic diffraction peaks of TiN.
[0065] Figure 3 The X-ray photoelectron spectrum shows that there are five elements, Cd, S, Se, Ti and N, in the CdS / CdSe / TiN nanosheet array, proving the successful preparation of the CdS / CdSe / TiN nanosheet array.
[0066] Figure 4This is a scanning electron microscope image. As can be seen from the figure, the scanning electron microscope of pure CdS Figure 4 (a, b) show a smooth nanosheet structure with vertical orientation growth; 4 (c, d) after depositing CdSe, the sample still maintains the nanosheet morphology, the surface of the nanosheet is rougher, and the thickness of the sheet structure increases slightly; 4 (e, f) after loading TiN nanoparticles, the overall structure of CdS / CdSe does not change significantly and still maintains the nanosheet morphology. TiN nanoparticles are loaded on the CdS / CdSe surface and slightly agglomerated at the junction of the nanosheets.
[0067] Figure 5 Transmission electron microscope morphology, high resolution and element distribution map. Figure 5 a As can be seen, the CdS nanosheet array is completely covered by CdSe nanoparticles, and TiN nanoparticles are loaded on the surface of the CdS / CdSe heterostructure; Figure 5 The high-resolution transmission electron microscopy image (b) shows three different and clear lattice fringes, which correspond to the (200) crystal plane of TiN, the (110) crystal plane of CdSe, and the (111) crystal plane of CdS. Figure 5 (ch) shows that the distribution patterns of Cd, S, Se, Ti and N elements are consistent with the morphology of CdS / CdSe / TiN nanosheet arrays.
[0068] Figure 6 is the light absorption and light capture efficiency curve. Figure 6 a It can be seen that after compounding with CdSe, the absorption edge of the CdS nanosheet array widens from 540 nm to 690 nm; after loading with TiN, the light absorption range of the CdS / CdSe / TiN heterostructure is further broadened, and it has strong light absorption ability in the wavelength range of 300-800 nm. Figure 6 b Light capture efficiency curve shows that the loading of CdSe and TiN improves the light capture efficiency of CdS.
[0069] Figure 7 is the comparison curve of photocurrent density and external bias voltage photoelectric conversion efficiency. Figure 7 The photocurrent density-time curve shown in a shows that all the tested samples have very sensitive photoresponse characteristics. Among them, the photocurrent density of the pure CdS nanosheet array is 2.2 mA cm -2 After the deposition of CdSe nanoparticles, the photocurrent density of the prepared CdS / CdSe nanosheet array increased significantly, reaching 6.2 mA·cm -2 , which is 2.82 times that of pure CdS nanosheet arrays. When loaded with TiN nanoparticles, the photocurrent density of the CdS / CdSe / TiN nanosheet array reaches up to 9.8 mA·cm -2, which is 4.26 times that of pure CdS nanosheet arrays. Figure 7 The linear sweep voltammetric characteristic curve (b) shows that the photocurrent density of all samples increases with the increase of applied bias voltage, and the photocurrent density of CdS / CdSe / TiN nanosheet array increases most significantly. Figure 7 From the external bias photoelectric conversion efficiency curve shown in c, it can be seen that the external bias photoelectric conversion efficiency of the pure CdS nanosheet array is as high as 1.98%; after depositing CdSe nanoparticles, the external bias photoelectric conversion efficiency of the prepared CdS / CdSe nanosheet array reaches a maximum of 3.75%, which is 1.89 times that of the pure CdS nanosheet array; after loading TiN nanoparticles, the bias photoelectric conversion efficiency of the CdS / CdSe / TiN nanosheet array reaches a maximum of 6.02%, which is 3.04 times that of the pure CdS nanosheet array.
[0070] Figure 8 is the hydrogen production performance comparison curve. Figure 8 The curve of hydrogen production and time shown in a shows that under continuous visible light irradiation for 2 hours, the hydrogen production per unit area of CdS, CdS / CdSe and CdS / CdSe / TiN nanosheet arrays is linearly correlated with the illumination time, which indicates that the prepared sample electrodes have stable hydrogen production capabilities. Figure 8 The histogram of hydrogen production rates of CdS, CdS / CdSe and CdS / CdSe / TiN nanosheet arrays shown in b shows that the CdS / CdSe / TiN nanosheet array has the highest hydrogen production rate, reaching 109 μmol·cm -2 ·h -1 , respectively CdS / CdSe (75.6 μmol·cm -2 ·h -1 ) and CdS (37.1 μmol·cm -2 ·h -1 ) are 1.44 and 2.93 times that of the nanosheet array.
[0071] Fig. 9The schematic diagram of the high-performance photoelectrocatalytic water splitting hydrogen production by the cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material prepared in the embodiment of the present invention. The loading of semiconductor CdSe with a narrow bandgap and TiN with a wide spectrum plasma resonance effect expands the light absorption range of CdS, significantly improving the utilization rate of light energy; the Type-II energy level matching formed between CdS and CdSe realizes the effective separation and transmission of photogenerated carriers; TiN generates hot electrons due to the SPR effect and injects them into the conduction band of CdSe, increasing the number of photogenerated electrons; the Schottky junction formed at the interface of TiN and CdSe inhibits the recombination of photogenerated carriers and prolongs the carrier lifetime. Therefore, the photoelectrocatalytic water splitting hydrogen production performance of CdS / CdSe / TiN nanosheet array is significantly improved.
[0072] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material, characterized in that: The steps include: Step 1: Preparation of two-dimensional CdS nanosheet arrays using a one-step hydrothermal method First, a CdSO4 aqueous solution is added to a beaker, and then ammonia water is added dropwise under stirring. During this process, the mixed solution first becomes turbid and then clear, and then stirring is continued to obtain a mixed solution A; then, CTAB is added to the mixed solution A, and stirring is continued to obtain a mixed solution B; then, a CH4N2S aqueous solution is added to the mixed solution B, and stirring is continued to obtain a mixed solution C; finally, the mixed solution C is transferred to the inner tank of the reactor, and the FTO conductive glass is placed in the inner tank of the reactor with the conductive surface facing downward and tilted to perform a hydrothermal reaction. After the hydrothermal reaction, the sample is taken out, washed with deionized water, and then dried to obtain a two-dimensional cadmium sulfide nanosheet array FTO@CdS; Step 2: Preparation of two-dimensional CdS nanosheet array / CdSe nanoparticle heterostructures using a continuous ion layer adsorption reaction method First, the FTO@CdS in step 1 is immersed in a Cd(NO3)2 solution, and then washed in anhydrous ethanol; after drying, the sample is immersed in a Na2SeO3 aqueous solution, and finally washed in deionized water. After such steps are repeated 10-50 times, a two-dimensional cadmium sulfide nanosheet array / cadmium selenide nanoparticle heterostructure FTO@CdS / CdSe is obtained; Step 3: Preparation of cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material by spin coating TiN nanoparticles were further loaded on the surface of FTO@CdS / CdSe by spin coating. First, TiN was dispersed in anhydrous ethanol and then ultrasonically treated to make it evenly dispersed to obtain a TiN precursor solution. Finally, 500 μL of the TiN precursor solution was vertically dropped on the surface of FTO@CdS / CdSe and spin coating was performed to obtain a cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material FTO@CdS / CdSe / TiN.
2. The method for preparing a cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material according to claim 1, characterized in that: In step 1, the concentration of CdSO4 aqueous solution is 0.1 M, and the amount of CdSO4 aqueous solution is 10-20 mL; the concentration of ammonia water is 25wt%, and the amount of ammonia water is 1-10 mL; the concentration of CH4N2S aqueous solution is 0.1 M, and the amount of CH4N2S aqueous solution is 10-20 mL; the amount of CTAB is 0.005-0.01 g.
3. The method for preparing a cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material according to claim 2, characterized in that: In step 1, the amount of CdSO4 aqueous solution used is 18 mL; the amount of ammonia water used is 4 mL; the amount of CH4N2S aqueous solution used is 18 mL; and the amount of CTAB used is 0.0072 g.
4. The method for preparing a cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material according to claim 1, characterized in that: The hydrothermal condition of the reactor in step 1 is 80-150° C. for 10-40 min.
5. The method for preparing a cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material according to claim 1, characterized in that: In step 2, the solvent in the Cd(NO3)2 solution is a mixed solution of 30wt% water and 70wt% anhydrous ethanol; the specific steps of step 2 are as follows: first, immerse the FTO@CdS in step 1 in a 0.1 M Cd(NO3)2 solution for 10-30s, and then wash it in anhydrous ethanol for 10-30s; after drying, immerse the sample in a 0.1 M Na2SeO3 aqueous solution at 70°C for 10-30s, and finally, wash it in deionized water for 10-30s. After 10-50 cycles of this, a two-dimensional cadmium sulfide nanosheet array / cadmium selenide nanoparticle heterostructure FTO@CdS / CdSe is obtained.
6. The method for preparing a cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material according to claim 1, characterized in that: In step 2, the contact time of each material is 20 s, the temperature of the Na2SeO3 aqueous solution is 50~90℃, and the number of cycles is 5-50 times.
7. The method for preparing a cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material according to claim 1, characterized in that: In step 3, the average particle size of the TiN nanoparticles is 20 nm; the mass concentration of the TiN precursor solution is 0.2-0.6 mg / mL, and the ultrasonic condition is 100-200 W for 20-60 min.
8. The method for preparing a cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material according to claim 1, characterized in that: The spin coating conditions in step 3 are firstly to spin coat at a low speed of 1000-2000 r / min for 10-20 s, and then to spin coat at a high speed of 3000-4000 r / min for 20-40 s; the loading amount of TiN nanoparticles is adjusted by controlling the number of spin coating to 10-100 times.
9. The cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material prepared according to the method for preparing a cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material according to any one of claims 1 to 8.
10. Application of the cadmium sulfide / cadmium selenide / titanium nitride two-dimensional structure photoelectrocatalytic material according to claim 9 for photoelectrocatalytic decomposition of water to produce hydrogen.
Citation Information
Patent Citations
Preparation and application of photoelectrochemical sensor based on cadmium sulfide nanoparticle / titanium dioxide nanowire array composite material
CN112666237A
QWLED based on nanoplate heterostructure CdS / CdTe / CdS quantum well light-emitting layer and preparation method thereof
CN115776823A